Polysaccharide-based sustainable hydrogel spheres for controlled release of agricultural inputs - Antunes, Débora R. [UNESP]; Forini, Mariana M.L.H. [UNESP]; Biscalchim, Érica R. [UNESP]; Lima, Pedro H.C. [UNESP]; Cavalcante, Luiz A.F. [UNESP]; Teixeira Filho, Marcelo C.M. [UNESP]; Tripathi, Durgesh K.; Caballero, Javier Pitti; Grillo, Renato [UNESP] (Elsevier, 2024)
Producing food in quantity and quality to meet the growing population demand is a challenge for the coming years. In addition to the need to improve the use and efficiency of conventional agricultural inputs, we face climate change and disparity in access to food. In this context, creating innovative, efficient, and ecologically approaches is necessary to transform this global scenario. Several delivery systems are being developed to encapsulate agrochemicals, aiming to improve the controlled release of active ingredients and protect them against environmental biotic and abiotic factors. Among these systems, hydrogel spheres are particularly notable for their ability to be fabricated from biodegradable materials, allowing the encapsulation of molecules, nanomaterials, and even organisms (e.g., bacteria and fungi). This review provides an overview of the latest progress in developing polysaccharide-based hydrogel spheres for agriculture. In addition, we describe methods for preparing hydrogel spheres and discuss the encapsulation and release of agricultural inputs in the field. Finally, we put hydrogel spheres into perspective and seek to highlight some current challenges in the field to spark new inspiration and improve the development of environmentally friendly and cost-effective delivery systems for the agricultural sector.
Esferas de hidrogel sustentáveis à base de polissacarídeos para liberação controlada de insumos agrícolas
Keywords: Polysaccharide beads; Agrochemicals; Controlled release; Encapsulation; Sustainable agriculture; Hydrogels